Potato Physiological Disorders - Brown Center and Hollow Heart - Lincoln Zotarelli; Chad Hutchinson; Seth Byrd; Douglas Gergela; Diane L. Rowland (EDIS)
Brown center and hollow heart are internal noninfectious physiological disorders of the potato tuber. Brown center is characterized by a region of cell death in the pith of the tuber that results in brown tissue. Hollow heart is characterized by a star- or lens-shaped hollow in the center of the tuber. This revised 2-page fact sheet was written by L. Zotarelli, C. Hutchinson, S. Byrd, D. Gergela, and D. L. Rowland, and published by the UF Department of Horticultural Sciences, May 2012.